2015
DOI: 10.1016/j.neubiorev.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

How fast and how often: The pharmacokinetics of drug use are decisive in addiction

Abstract: How much, how often and how fast a drug reaches the brain determine the behavioural and neuroplastic changes associated with the addiction process. Despite the critical nature of these variables, the drug addiction field often ignores pharmacokinetic issues, which we argue can lead to false conclusions. First, we review the clinical data demonstrating the importance of the speed of drug onset and of intermittent patterns of drug intake in psychostimulant drug addiction. This is followed by a review of the prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
120
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(141 citation statements)
references
References 135 publications
8
120
0
2
Order By: Relevance
“…Although this is the first report of a progressive increase in motivation for cocaine with prolonged IntA experience, Zimmer et al (2012) previously reported that rats with a history of IntA cocaine self-administration had a significantly higher P max than those with LgA experience, despite consuming much less drug (they did not report α values). Collectively, these findings are consistent with the notion that, “an intermittent pattern of use, more than the amount of drug used,” (Allain et al, 2015, p. 175) may be especially important in the development of addiction.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Although this is the first report of a progressive increase in motivation for cocaine with prolonged IntA experience, Zimmer et al (2012) previously reported that rats with a history of IntA cocaine self-administration had a significantly higher P max than those with LgA experience, despite consuming much less drug (they did not report α values). Collectively, these findings are consistent with the notion that, “an intermittent pattern of use, more than the amount of drug used,” (Allain et al, 2015, p. 175) may be especially important in the development of addiction.…”
Section: Discussionsupporting
confidence: 86%
“…In addition to dose, the temporal patterns by which drugs reach the brain (pharmacokinetics) can powerfully influence their ability to change brain and behavior (Allain et al , 2015; Robinson and Becker, 1986). We asked, therefore, how prolonged experience with a newly developed intermittent access self-administration procedure (IntA; Zimmer et al, 2012), which produces repeated spikes in brain cocaine concentrations, changes motivation for cocaine, as assessed using behavioral-economic indicators of cocaine demand (Bentzley et al , 2013; Hursh and Silberberg, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations